Cutaneous vasculitis in primary Sjögren syndrome: classification and clinical significance of 52 patients (2004)
ABSTRACT: To analyze the different clinical and histologic types of cutaneous vasculitis in patients with primary Sjögren syndrome (SS), we investigated the clinical and immunologic characteristics of 558 consecutive patients with primary SS from our units and selected those with clinical evidence of cutaneous lesions, excluding drug reactions and xeroderma. All patients fulfilled 4 or more of the diagnostic criteria for SS proposed by the European Community Study Group in 1993. A total of 89 (16%) patients presented with cutaneous involvement (88 female patients and 1 male; mean age, 51.8 yr). The main cutaneous involvement was cutaneous vasculitis, present in 52 (58%) patients. There were 51 (98%) female patients and 1 (2%) male, with a mean age at diagnosis of cutaneous vasculitis of 51 years (range, 20-80 yr). Fourteen presented with cryoglobulinemic vasculitis, 11 with urticarial vasculitis, and the remaining 26, with cutaneous purpura not associated with cryoglobulins. A skin biopsy specimen was obtained in 38 patients (73%). Involvement of small-sized vessels was observed in 36 (95%) patients (leukocytoclastic vasculitis), while the remaining 2 (5%) presented with medium-sized vessel vasculitis (necrotizing vasculitis). Patients with cutaneous vasculitis had a higher prevalence of articular involvement (50% vs 29%, p = 0.044), peripheral neuropathy (31% vs 4%, p < 0.001), Raynaud phenomenon (40% vs 15%, p = 0.008), renal involvement (10% vs 0%, p = 0.028), antinuclear antibodies (88% vs 60%, p = 0.002), rheumatoid factor (78% vs 48%, p = 0.004), anti-Ro/SS-A antibodies (70% vs 43%, p = 0.011), and hospitalization (25% vs 4%, p = 0.005) compared with SS patients without vasculitis. Six (12%) patients died, all of whom had multisystemic cryoglobulinemia. In conclusion, cutaneous involvement was detected in 16% of patients with primary SS, with cutaneous vasculitis being the most frequent process. The main characteristics of SS-associated cutaneous vasculitis were the overwhelming predominance of small versus medium vessel vasculitis and leukocytoclastic versus mononuclear vasculitis, with a higher prevalence of extraglandular and immunologic SS features. Small vessel vasculitis manifested as palpable purpura, urticarial lesions, or erythematosus maculopapules, with systemic involvement in 44% of patients in association with cryoglobulins in 30%. Life-threatening vasculitis was closely related to cryoglobulinemia.